The Mathematics Reasoning Skill of X Graders based on Entrepreneurship Character on a Brain-based Learning with RME Approach - Munir, Misbahul; Kartono, Kartono; Junaedi, Iwan (Unnes Journal of Mathematics Education Research, 2023)
This research described the mathematics reasoning skill of learners taught by brain-based learning with an RME approach based on the entrepreneurship character. This descriptive qualitative research took the research 32 subjects of X graders from BDP 2 Vocational High School Swadaya Semarang in the academic year of 2021/2022. The researchers collected the data with a questionnaire, observation, documentation, and interview. The results showed the learners' mathematics reasoning skills based on their entrepreneurship characters taught by brain-based learning with the RME approach were varied. The researchers analyzed the data by reducing, displaying, triangulating, interpreting, and verifying the data. The results showed the entrepreneurship characteristics of the learners were categorized into high and moderate. The learners' mathematics reasoning skills varied based on their entrepreneurship character.